Lysine blockage of milk proteins in infant formula impairs overall protein digestibility and peptide release - Zenker, Hannah E.; Van Lieshout, Glenn A.A.; Van Gool, Martine P.; Bragt, Marjolijn C.E.; Hettinga, Kasper A. (Food and Function, 2020)
During heat processing of milk and dairy products, for example infant formula, the Maillard reaction occurs. In vitro and animal studies suggest that Maillard reaction induced lysine blockage impairs protein digestibility. Most studies that investigate the effect of glycation on protein digestion use a mixture of isolated milk protein with reducing sugars. In this study, infant formulas with 6.5%, 8.4%, 11.2%, 14.8%, 20.8%, and 44.5% of blocked lysine (BL) were digested in an in vitro infant digestion model and tested for protein hydrolysis and peptide release. OPA (o-phthalaldehyde) assay was used to assess the degree of protein hydrolysis. SDS-PAGE was conducted to monitor the hydrolysis of specific proteins. Peptides formed after gastric and intestinal digestion were identified by LC/MS. Protein hydrolysis of the 6.5% BL sample was significantly higher after 10 minutes of intestinal digestion compared to all other samples. Most differences were observed after intestinal digestion. A significant change in peptide patterns was observed for the 45% BL sample resulting in a relatively higher number of peptides with more than 14 amino acids. Mainly casein-derived peptides were affected. Overall, the average peptide length was significantly increased for the 44.5% BL glycated product (on average 10.2 amino acids for 6-21% BL vs. 11.4 amino acids for 45% BL; p < 0.001). In conclusion, glycation of milk proteins in an infant formula product can impair overall protein digestibility. These findings emphasize the importance of mild processing and having low BL levels in infant formula to ensure optimal digestion of proteins.
Created from Fastlane, Scopus look-up